Middle East and North African Health Informatics Association (MENAHIA) - Tara, Mahmood; Adel, Taweel; Dari, Alhuwail; Al Thani, Dena A.; Al-Jafar, Eiman; Abu Hamra, Eman; Ghazal, Hassan; Wahba, Hoda; Bahaadinbeigy, Kambiz; AlKhalifa, Khalid; Joseph, Leena; Zeroug, Mohamed; Odeh, Mohammad Bani; Alhefzi, Mohammed I.; Hamdi, Mounir; Househ, Mowafa; Al-Shorbaji, Najeeb; El Hassan, Osama; Al-Salmi, Salim Abdullah; Amara, Tamer; Sari, Zoubir (Yearbook of Medical Informatics, 2021)
The unforeseen pandemic of COVID-19 forced all countries worldwide to appreciate digital solutions and their potential contributions in managing such outbreaks. Countries began to share their knowledge and ongoing experiences on how to employ the latest technologies to trace infected cases, warn people on potential danger, increase social and population awareness, and how to provide effective and efficient telehealth services. MENAHIA (The Middle East and North Africa Health Informatics Association), established in 2018, as a new IMIA regional chapter which has started regional work in several areas of collaboration and knowledge sharing, particularly focused on the common basis of MENA countries’ needs towards health informatics solutions regarding COVID-19 crisis management. This article briefly presents health informatics activities and prospects by countries of the Region with a non-exclusive focus on the COVID-19 pandemic. Needless to say, not all the countries have reported using this platform, and some may have reported through other venues.
Keywords: COVID-19; digital health; health informatics; Middle East and North Africa; MENAHIA; International Medical Informatics Association; IMIA; National eHealth societies; Algeria; Bahrain; Egypt; Iran; Jordan; Kuwait; Morocco; Oman; Palestine; Qatar; Saudi Arabia; United Arab Emirates